2017
DOI: 10.1007/s00403-017-1718-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring acne using Coproporphyrin III, Protoporphyrin IX, and lesion-specific inflammation: an exploratory study

Abstract: Propionibacterium acnes: (P. acnes) produce Porphyrins; however, fluorescence measurement of Porphyrins from Ultraviolet-A (UVA) images has failed to establish a correlation. Acne clinical research and imaging has ignored the spectral excitation-emission characteristics and the exact pattern of the Porphyrins synthesized by P. acnes. In this exploratory study, for the first time, the possible relationships of Coproporphyrin III (CpIII) and Protoporphyrin IX (PpIX) fluorescence as well as acne lesion-specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
0
24
0
2
Order By: Relevance
“…One of the characteristics of acne is the colonization of hair follicles by bacteria Propionibacterium acnes (P. acnes) (Williams et al, 2012;Zouboulis, 2014). Several studies (Patwardhan et al, 2017;Xu et al, 2018) have shown that substances secreted by P. acnes called porphyrins are the cause of acne lesions fluorescence. Porphyrins absorbe ultraviolet (UV) light and emit red fluorescence in response (Borelli et al, 2006;Youn, Kim, Lee, Kim, & Park, 2009).…”
Section: Fluorescence Imagesmentioning
confidence: 99%
“…One of the characteristics of acne is the colonization of hair follicles by bacteria Propionibacterium acnes (P. acnes) (Williams et al, 2012;Zouboulis, 2014). Several studies (Patwardhan et al, 2017;Xu et al, 2018) have shown that substances secreted by P. acnes called porphyrins are the cause of acne lesions fluorescence. Porphyrins absorbe ultraviolet (UV) light and emit red fluorescence in response (Borelli et al, 2006;Youn, Kim, Lee, Kim, & Park, 2009).…”
Section: Fluorescence Imagesmentioning
confidence: 99%
“…[11,12] Indeed, a large number of molecules have been developed to prevent comedogenicity. [13,14] In vivo fluorescence imaging has also been widely employed for acne skin visualization because P acnes produces porphyrins, a family of pro-inflammatory metabolites [15,16] which exhibits a strong fluorescence under A-light ultraviolet (UVA) excitation. [17][18][19] Recently Xu et al confirmed through a systematic analysis that the skin red autofluorescence comes from P acnes porphyrin and that pure sebum present any red autofluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Patwardhan et al pointed out that the porphyrin most produced by P acnes, Coproporphyrin III, presents a fluorescence emission between 570 and 630 nm. [15] However, many questions remain open, especially is P acnes colonization in the pilosebaceous unit starting as soon as microcomedone stage? And is it associated with a clear bacterial metabolism?…”
Section: Introductionmentioning
confidence: 99%
“…Look around the world, and with changes in latitude, altitude, water levels, sunlight intensity, it all has an impact on the species that grow and thrive there. On our faces, fluorescence photography can show the location of bacteria on acne prone skin, and can even differentiate species based on how the porphyrins they produce fluoresce [4]. Pores on the face which are next to one another, only fractions of a mm apart, can have different bacterial populations.…”
mentioning
confidence: 99%